"Dimensionnement du Réseau d’Assainissement Cité El KHOBNA Commune TERIFAOUI Daira HASSI KHALIFA wilaya d'EL OUED " - ليحيو, توفيق; غربي, فتحي (My University, 2020)
The aim of our study is to size our sanitation network with the technical standards adopted in order to meet the needs of everyday man and the maintenance of his health, as well as the organization of life. daily regardless of local domestic wastewater and rainwater. الهدف من دراستنا هو تحديد أبعاد شبكة الصرف الصحي لدينا بالمعايير الفنية المعتمدة من أجل تلبية احتياجات الإنسان اليومية والحفاظ على صحته ، وكذلك تنظيم الحياة. يوميًا بغض النظر عن مياه الصرف الصحي المحلية ومياه الأمطار.
Conception et diagnostic du système d'AEP et d'Assainissement- مذكرة ماستر تخصص
Keywords: design, network, sanitation, Wastewater.; تصميم ، شبكة، التطهير، المياه المستعملة المنزلية ، مياه الأمطار